PENGARUH FAKTOR FINANSIAL, FAKTOR SOSIAL, DAN FAKTOR PSIKOLOGIS TERHADAP KINERJA KARYAWAN PADA LPD KESIMAN DENPASAR - Yenny Verawati; Saptarini Widyawati (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2017)
Human resources must be well managed to improve organizational effectiveness and efficiency. performance or perfomance is a description of the level of achievement of the implementation of an activity or policy program in realizing organizational goals, goals, vision and mission as outlined in strategic planning. Companies need to make employees work well and have a loyalty to the company and have a high work motivation. The purpose of this study is 1) to determine the effect of financial factors on employee performance 2) to determine the influence of social factors on employee performance 3) to determine the effect of psychological factors on employee performance. Data analysis techniques used in this study are multiple linear regression, determination, Test F and Test t. Interesting findings from the results of this study are financial factors that do not significantly affect employee performance. While the influence of social factors and psychological factors confirm the results of previous research that social factors and psychological factors have a significant positive effect on employee performance.